BREAKING THE SILENCE : PSYCHOLOGICAL SAFETY AS A BUFFER AGAINST THE EFFECT OF FEAR OF EVALUATION FROM SUPERVISOR ON COMMUNICATION APPREHENSION - Tzu-Yi Chuang (PEOPLE: International Journal of Social Sciences, 2026)
In the workplace, "evaluation" is omnipresent. Evaluation and feedback are key drivers of employee and organizational development. However, prior research has rarely explored the negative impact of employees’ fear of negative evaluation. Therefore, based on the perspective of the Feeling-as-Information Theory (FAIT), this study aims to investigate the relationship between fear of negative evaluation from supervisors, increased communication apprehension, and subsequent defensive silence. In addition, drawing on Social Cognitive Theory, the study examines the moderating role of perceived psychological safety in the relationship between fear of negative evaluation from supervisors and communication apprehension. A two-wave questionnaire survey (with a two-week interval) was conducted among full-time employees across various industries in Taiwan. A total of 239 valid responses were collected. The hypotheses were tested using PROCESS Macro. The results revealed that: (1) fear of negative evaluation from supervisors is positively associated with communication apprehension; (2) communication apprehension mediates the relationship between fear of negative evaluation from supervisors and defensive silence; (3) perceived psychological safety weakens the positive relationship between fear of negative evaluation from supervisors and communication apprehension; and (4) perceived psychological safety negatively moderates the indirect effect of fear of negative evaluation from supervisors on defensive silence via communication apprehension.